Rural Cooperative Youth in Argentina : The Coninagro Youth Table (2010-2021) - de Arce, Alejandra; Mateo, Graciela (Cooperativismo & Desarrollo, 2022)
Cooperativism is committed to youth participation to ensure the survival and renewal of this economic model. Argentine agro-cooperatives promote the training of young people. These actions are meant to look forward to the generational change in the leadership, to the transfer of productive and management activities in rural farms and to form as citizens committed to the development of their communities. The article proposes a case study based on the collation of various sources (specialized bibliography; cooperative periodicals; official publications, agricultural censuses and surveys of Social Economy agencies; statutes; regulations; official website, interviews to key informants) and a qualitative methodology. We use Content analysis to reconstruct the antecedents and the conformation of the CONINAGRO Youth Committee, its strategies, missions, visions, the composition of the leadership in a gender key and the ways in which young people are trained for the change in leadership. Throughout our investigation we reconstructed the activities carried out by this youth organization, and were able to perceive the obstacles it faced. Some of them were not recognized or perceived by the youth who tended to reproduce behaviors assumed by CONINAGRO. Despite the emphasis with which agro-cooperatives insist from the discourse and through different strategies in youth training, it has been verified that gender and generational inequalities persist in this model, especially in access to decision-making spaces of this confederate central.